The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2001
DOI: 10.1046/j.1460-9592.2001.00191.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome of Patients Who Develop PAF After CABG Surgery

Abstract: This was a retrospective analysis of patients who had CABG surgery at our hospital over a 12-month period to determine the intermediate-term prognosis of those who had developed PAF after their operation before hospital discharge. Of 317 patients who were operated by a single surgical group, 116 (37%) had AF postoperatively of whom 112 had the paroxysmal form. Of these, 36 were treated with class I or III antiarrhythmic drugs and rate control drugs (group 1) and 76 were treated with rate control alone (group 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
41
0
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(47 citation statements)
references
References 13 publications
1
41
0
3
Order By: Relevance
“…Other abbreviations as in Table 1. 26 Elahi et al reported a POAF incidence of 14% in the immediate postoperative period, 2% at 6 weeks and 1% at 1 year postoperatively. 5 These studies, however, collected information retrospectively, and in the Elahi et al study, data on late follow-up were collected via telephone national guidelines encouraging a prescription of antiplatelet therapy only.…”
Section: 56mentioning
confidence: 97%
“…Other abbreviations as in Table 1. 26 Elahi et al reported a POAF incidence of 14% in the immediate postoperative period, 2% at 6 weeks and 1% at 1 year postoperatively. 5 These studies, however, collected information retrospectively, and in the Elahi et al study, data on late follow-up were collected via telephone national guidelines encouraging a prescription of antiplatelet therapy only.…”
Section: 56mentioning
confidence: 97%
“…[1][2][3] Postoperative AF after cardiac surgery can cause a number of complications, including congestive heart failure, stroke, and hemodynamic instability. It is responsible for increased hospital costs and prolonged hospitalization.…”
mentioning
confidence: 99%
“…It is responsible for increased hospital costs and prolonged hospitalization. [1][2][3] This tachyarrhythmia usually occurs within 1 week after cardiac surgery and generally resolves over the first 3 weeks after cardiac surgery. Previous studies have shown that the peak incidence of early postoperative AF is on the second postoperative day after CABG.…”
mentioning
confidence: 99%
“…It typically occurs between the first and the fifth day following surgery with frequency peak on the second day [2]. Although it is well tolerated in the majority of the patients [3], AF can result in hemodynamic instability, especially in those patients with left ventricular diastolic dysfunction because they present a reduced tolerance to the loss of atrial contraction [4]. Limiting the use of betablockers and amiodarone [5,6], as a prophylactic pharmacological measurement of postoperative AF, have induced studies regarding prophylactic nonpharmacological measurements.…”
Section: Introductionmentioning
confidence: 99%